Vangl2 coordinates cell rearrangements during gut elongation. Issue 7 (24th May 2019) - Dush, Michael K.; Nascone‐Yoder, Nanette M.
Abstract: Background: The embryonic gut tube undergoes extensive lengthening to generate the surface area required for nutrient absorption across the digestive epithelium. In Xenopus, narrowing and elongation of the tube is driven by radial rearrangements of its core of endoderm cells, a process that concomitantly opens the gut lumen and facilitates epithelial morphogenesis. How endoderm rearrangements are properly oriented and coordinated to achieve this complex morphogenetic outcome is unknown. Results: We find that, prior to gut elongation, the core Wnt/PCP component Vangl2 becomes enriched at both the anterior and apical aspects of individual endoderm cells. In Vangl2‐depleted guts, the cells remain unpolarized, down‐regulate cell‐cell adhesion proteins, and, consequently, fail to rearrange, leading to a short gut with an occluded lumen and undifferentiated epithelium. In contrast, endoderm cells with ectopic Vangl2 protein acquire abnormal polarity and adhesive contacts. As a result, endoderm cells also fail to rearrange properly and undergo ectopic differentiation, resulting in guts with multiple torturous lumens, irregular epithelial architecture, and variable intestinal topologies. Conclusions: Asymmetrical enrichment of Vangl2 in individual gut endoderm cells orients polarity and adhesion during radial rearrangements, coordinating digestive epithelial morphogenesis and lumen formation with gut tube elongation. Key Findings: Vangl2 expression is apically and anteriorly polarized in rearranging endoderm cells during gut morphogenesis. Vangl2 is required for normal endoderm cell shape, adhesion and microtubule architecture. Polarized Vangl2 is required for the cell rearrangements that drive gut elongation, lumen formation and epithelial morphogenesis.